Dampak Kecanduan Judi Online Terhadap Perilaku Akademik Mahasiswa Bimbingan dan Konseling Universitas Sanata Dharma - Fonda Mega Mahilda; Antonius Ian Bayu Setiawan (STIKes Ibnu Sina Ajibarang, 2025)
The aim of this study is to : 1) understand and describe the academic behavior of students who are addicted to online gambling, 2) as well as to identify the impacts affecting the academic performance of those students. This research employs a qualitative method, with data collection conducted through non-participant observation and interviews. The subjects of the study are focused on Guidance and Counseling students at Sanata Dharma University who are addicted to online gambling. The data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that online gambling disrupts students' cognitive abilities, leading to cognitive fatigue and negatively affecting their academic behavior, which in turn disrupts their academic activities and results in a decline in both academic and non-academic performance.